Can we reduce the epidemic of elbow injuries in youth throwers? - Padaki, A. S.; Ahmad, C. S. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
As participation in youth sports continues to increase across the nation, more adolescents are participating in Little League baseball in the United States than ever before. Accompanying this increased participation is an epidemic of upper extremity injuries in young throwers. In this Viewpoint, the authors discuss the impetus behind the youth thrower elbow injury epidemic and how to best evaluate these patients.